Identification and Molecular Characterization of a Novel Hordeivirus Associated With Yellow Mosaic Disease of Privet (Ligustrum vulgare) in Europe - Reynard, Jean-Sébastien; Turco, Silvia; Brodard, Justine; Kellenberger, Isabelle; Maclot, François; Schumpp, Olivier; Gugerli, Paul; Pooggin, Mikhail M. (Frontiers in Microbiology, 2021)
Wild plants serve as a large reservoir of known and yet-unknown viruses and as a source of viral pathogens of cultivated plants. Yellow mosaic disease of forest shrub Ligustrum vulgare (privet) was recurrently observed in Europe for more than 100 years. Using a universal virus identification approach based on deep sequencing and de novo assembly of viral small interfering (si)RNAs we identified a causative agent of this disease in Switzerland and reconstructed its complete 3-segmented RNA genome. Notably, a short 3’-terminal common region (CR) attached to each segment via a ~53-71 nucleotide poly(A) tract, as determined by RT-PCR sequencing, was initially identified as an orphan siRNA contig with conserved tRNA-like secondary structure. Phylogenomic analysis classified this virus as a novel member in the genus Hordeivirus of family Virgaviridae, which we named ligustrum mosaic virus (LigMV). Similar to other hordeiviruses, LigMV formed rod-shape virions (visualized by electron microscopy), was transmitted through seeds and could also be mechanically transmitted to herbaceous hosts Chenopodium quinoa and Nicotiana benthamiana. Blot hybridization analysis identified genomic and subgenomic RNAs, sharing the 3’-CR and likely serving as monocistronic mRNAs for seven evolutionarily-conserved viral proteins including two subunits of viral RNA-dependent RNA polymerase, coat protein, triple gene block proteins mediating viral movement and cysteine-rich suppressor of RNA silencing. Analysis of size, polarity, and hotspot profiles of viral siRNAs suggested that they are produced by the plant antiviral Dicer-like (DCL) proteins DCL2 and DCL4 processing double-stranded intermediates of genomic RNA replication. Whole genome sequencing of French and Austrian isolates of LigMV revealed its genetic stability over a wide geographic range (> 99 % nucleotide identity to Swiss isolates and each other), suggesting its persistence and spread in Europe via seed dispersal.